Green Technology Adoption, Complexity, and the Role of Public Policy: A Simple Theoretical Model - Sanjit Dhami (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider technology choices between green and brown technologies by firms. We use insights from complexity theory and also take account of true uncertainty in designing public policy. The green technology offers relatively higher returns to scale from adoption, and there are type-contingent differences among firms in their suitability for the green technology. We show that the long-run outcome is unpredictable despite there being no fundamental uncertainty in the model; small accidents of history can lead to large effects; and the final outcome is an 'emergent property' of the system. We describe the role of taxes and subsidies in facilitating adoption of the green technology. We also consider issues of the conflict between optimal Pigouvian taxes and green technology adoption; optimal temporal profile of subsidies; and the desirability of an international fund to provide technology assistance to poorer countries. Despite the simplicity of the framework, several novel results are demonstrated that typically do not arise in the standard analysis of the problem.
Keywords: D01; D21; D90; H32; 330; technology choice; climate change; complexity; lock-in effects; increasing returns; green subsidies; public policy; Pigouvian taxes; stochastic dynamics